TOURISM DEVELOPMENT CONDITIONS IN THE MUNICIPALITIES OF LITHUANIA - Narkūnienė, Ramutė; Gražulis, Vladimiras (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2018)
The authors of the paper discuss the tourism development conditions in the municipalities of Lithuania. The scientific problem - tourism development trends have not been studied at the local, municipality level in Lithuania and tourism in districts developed without a clear and long-term development strategy and consistent implementation of the programme. The aim of the research is to explore tourism development conditions in the municipalities of Lithuania. Objectives of the research are to characterize the factors influencing the development of tourism; to perform an analysis of the main factors of tourism development in Lithuania; to define the major factors of tourism management in the municipalities of Lithuania. Tourism development issues were discussed; the results of the research (an analysis of scientific literature and questionnaire survey, an analysis of strategic documents) were performed. The factors, which influence tourism the most are the human and financial resources, tourism infrastructure, the variety of tourism services, the virtual environment, the image of a tourism destination/ awareness, management of the tourism destination, the quality of tourism services and events. Tourism development in the municipalities of Lithuania is influenced by such factors, as the development of the tourism planning and management system, an adequate competence of human resources, cooperation between the public and private sectors, planning and organization, the legal framework for tourism, tourism projects development and implementation, a tourism development strategy and research in the tourism development area.